2013
DOI: 10.4314/ajtcam.v10i5.8
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antiosteoporotic effect of <i>Lepidium Sativum</i> and alendronate in glucocorticoid-induced osteoporosis in wistar rats

Abstract: Alendronate belongs to a class of drugs called bisphosphonates. Bisphosphonates (BP) therapy is a vital option to reduce the risk of bone fracture in people who suffer from osteoporosis. Yet, bisphosphonate have displayed several side effects. Lepidium sativum (LS) seeds have been used in traditional folk medicine to heal fractured bones. However, there is a dearth of information on the impact of LS on bone metabolism especially in cases of glucocorticoids induced osteoporosis. Therefore, the aim of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
8
16
0
Order By: Relevance
“…40 BALP, an indicator of bone formation secreted from osteoblasts, has been used to measure bone loss in patients with bone metabolic disorders and to confirm the role of osteoblasts on metabolic bone diseases. 41 GIOP reduced BALP levels, in accordance with other studies, 42 and ATV prevented the reduction of BALP serum levels. It has been reported that ATV can either not alter or slightly increase BALP serum levels, 43 explained by stimulation of bone morphogenetic protein-2 and induction of osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…40 BALP, an indicator of bone formation secreted from osteoblasts, has been used to measure bone loss in patients with bone metabolic disorders and to confirm the role of osteoblasts on metabolic bone diseases. 41 GIOP reduced BALP levels, in accordance with other studies, 42 and ATV prevented the reduction of BALP serum levels. It has been reported that ATV can either not alter or slightly increase BALP serum levels, 43 explained by stimulation of bone morphogenetic protein-2 and induction of osteoblast differentiation.…”
Section: Discussionsupporting
confidence: 91%
“…In the present work, we have to study the effect of Lactoferrin and alendronate on osteoporosis induced by glucocorticoid (prednisone) in females and males rats. From obtained results, we noticed the glucocorticoid caused the increase in serum calcium and the decrease in serum phosphorous levels, the similar result was obtained by (Elshal et al, 2013) showed that serum phosphorus concentration was significantly lower in glucocorticoid administration. On the other hand (Shomali and Fakhrzad, 2013) recorded in their study on rats an insignificant increase in calcium level in rats that treated with glucocorticoid.…”
Section: Discussionsupporting
confidence: 83%
“…Also, Yonemura et al, (1999)Stated that the oral dose of prednisolone administration increases serum calcium and ionized calcium levels, possibly mediated by suppressed bone formation, increased calcium absorption in the intestine, and impaired calcium excretion in the urine. Also, an increase of serum calcium after glucocorticoid administration might occur as a result of increased release of Calcium from bone tissues (Elshal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with either GC and/or ALD ameliorated the above-mentioned changes with variable degrees, with a net result of improved serum Ca, bone architecture, PTB, b-ALP and decreased TRAP in GC and GC+ALD groups compared to that of animals treated with alendronate alone. In conclusion, this study related findings present evidence supporting the probable benefits of L. sativum in reducing the burden of glucocorticoids on bone health [46].…”
Section: Antiosteoporotic Effect βsupporting
confidence: 79%